2016
DOI: 10.1051/e3sconf/20161000009
|View full text |Cite
|
Sign up to set email alerts
|

The process of fly ash magnetic separation impact on hydrothermal synthesis of zeolites

Abstract: Abstract. The aim of the experiment was modifying raw fly ash through the demagnetisation process and determining its influence on the efficiency of the synthesis of zeolite materials out of fly ash. A series of experiments have been performed on modified samples and, for the purpose of verification, on non-modified fly ash. No direct correlation has been confirmed in relation to synthesis efficiency as well as the type of obtained zeolite material. The research results indicate that the composition of fly ash… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…In the fusion method experiment (F650 0 C) the decrease of alkali amount influence on the synthesis product was tested. In preliminary experiments [11] it was fund that the use of fly ash to alkali ratio of value 2 in most cases did not result in obtaining zeolite as a product. The only case of zeolite crystallization in this fly ash/alkali ratio was the one performed in the temperature 650 0 C, which was the criteria of selecting this temperature as a synthesis parameter for testing increase of fly ash/alkali ratio up to value 3.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the fusion method experiment (F650 0 C) the decrease of alkali amount influence on the synthesis product was tested. In preliminary experiments [11] it was fund that the use of fly ash to alkali ratio of value 2 in most cases did not result in obtaining zeolite as a product. The only case of zeolite crystallization in this fly ash/alkali ratio was the one performed in the temperature 650 0 C, which was the criteria of selecting this temperature as a synthesis parameter for testing increase of fly ash/alkali ratio up to value 3.…”
Section: Resultsmentioning
confidence: 99%
“…Results of performed experiments indicate that it is possible to obtain zeolites of higher potential of application with the use of fly ash/alkali ratio 2. Related research [11] performed with the use of fusion method indicated that the use of higher fly ash/alkali ratio is not efficient in relation to zeolite crystallization. In the experiment performed in the temperature 550 0 C it was tested how does the change in fly ash/alkali ratio will influence the synthesis product.…”
Section: Data Analysis For Series Of Samples F650mentioning
confidence: 99%
See 1 more Smart Citation
“…Depending on the silicone to aluminum ratio of the raw material, faujasite is divided into X and Y. Zeolite X is obtained as a result of the synthesis of raw materials with the ratio between 2 and 3 [29], while zeolite Y with the ratio from 3 and more [31]. Zeolite Y, obtained under the conditions of zeolitization of sample S10, proves that the synthesis at the crystallization temperature of 90 o C is more favorable than at 60 o C [32].…”
Section: Resultsmentioning
confidence: 99%
“…CEC is a measurement of the number of cations in the channels by unit weight that may be replaced by other ions in solutions. The exchangeable cations of samples were replaced by NH4 + using 1M ammonium acetate [29]. The concentration of ammonium ions in solutions was determined with the use of ion chromatography.…”
Section: Characterization Methodsmentioning
confidence: 99%